Actinomycin X2, chất kháng sinh được phân lập từ quá trình lên men sinh tổng hợp Streptomyces microflavus. - Thu, Cao Văn; Hà, Bùi Việt; Kiệm, Phan Văn (Vietnam Journal of Chemistry, 2012)
From the ethyl acetate extract of the antibiotic biosynthesis fermentation by Streptomyces 15.29 (Streptomyces microflavus), actinomycin X2 was isolated by various chromatography methods. The chemical structure was determined from its spectral data in comparison with previous literature. This is the first report of NMR data of actinomycin X2.